Evaluation of the effects of selected phytochemicals on quorum sensing inhibition and in vitro cytotoxicity - Borges, Anabela (2014)
Quorum sensing (QS) is an important regulatory mechanism in biofilm formation and differentiation. Interference with QS can affect biofilm development and antimicrobial susceptibility. This study evaluates the potential of selected phytochemical products to inhibit QS. Three isothiocyanates (allylisothiocyanate - AITC, benzylisothiocyanate - BITC and 2-phenylethylisothiocyanate - PEITC) and six phenolic products (gallic acid - GA, ferulic acid - FA, caffeic acid - CA, phloridzin - PHL, (-) epicatechin - EPI and oleuropein glucoside - OG) were tested. A disc diffusion assay based on pigment inhibition in Chromobacterium violaceum CV12472 was performed. In addition, the mechanisms of QS inhibition (QSI) based on the modulation of N-acyl homoserine lactone (AHLs) activity and synthesis by the phytochemicals were investigated. The cytotoxicity of each product was tested on a cell line of mouse lung fibroblasts. AITC, BITC and PEITC demonstrated a capacity for QSI by modulation of AHL activity and synthesis, interfering the with QS systems of C. violaceum CviI/CviR homologs of LuxI/LuxR systems. The cytotoxic assays demonstrated low effects on the metabolic viability of the fibroblast cell line only for FA, PHL and EPI.